T1 mapping for assessment of myocardial injury and microvascular obstruction at one week post myocardial infarction. Issue 1 (January 2016) - Cameron, Donnie; Siddiqi, Nishat; Neil, Christopher J.; Jagpal, Baljit; Bruce, Margaret; Higgins, David M.; He, Jiabao; Singh, Satnam; Redpath, Thomas W.; Frenneaux, Michael P.; Dawson, Dana K.
Abstract: Objectives: To compare 3T T1 mapping to conventional T2 -weighted (T2 W) imaging for delineating myocardial oedema one week after ST-elevation myocardial infarction (STEMI), and to explore the confounding effects of microvascular obstruction (MVO) on each technique. Methods: T2 W spectral attenuated inversion recovery and native T1 mapping were applied in 10 healthy volunteers and 62 STEMI patients, and late gadolinium enhancement was included for infarct localisation at 1 week and at 6 months post-STEMI. Segmental T1 values and T2 W signal intensity ratios were calculated; oedema volumes and salvage indices were determined in patients using image thresholding—a receiver operator characteristic (ROC) derived T1 threshold, and a 2SD T2 W threshold; and the results were compared between patients with/without MVO ( n = 35/27). Results: Native T1 mapping delineated oedema with significantly better discriminatory power than T2 W—as indicated by ROC analysis (area-under-the-curve, AUC = 0.89 versus 0.83, p = 0.009; and sensitivity/specificity = 83/83% versus 73/73%). The optimal ROC threshold derived for T1 mapping was 1241 ms, which gave significantly larger oedema volumes than 2SD T2 W ( p = 0.006); with this threshold, patients with and without MVO showed similar oedema volumes, but patients with MVO had significantly poorer salvage indices ( p < 0.05) than those without. Neither method was significantly affected by MVO, the volume of which was seen to increase exponentially with infarct size. Conclusions: Native T1 mapping at 3T can delineate oedema one week post-STEMI, showing larger oedema volumes and better discriminatory power than T2 W imaging, and it is suitable for quantitative thresholding. Both techniques are robust against MVO-related magnetic susceptibility.